Exploring AI-Based Music Tool Affordances to Enhance Gen Z Creativity: A Study Using Affordance Theory in Papua - Padwa, Charles; Juita, Ratna; Inan, Dedi I.; Indra, Muhammad (Journal of Applied Informatics and Computing, 2025)
Artificial intelligence (AI) plays an important role in the world of music, especially for Generation Z who grew up in the digital age. However, understanding of how AI drives musical creativity in the context of music education is still limited, especially in West Papua and Papua. This study aims to analyze the influence of awareness, perception, and intention to use AI on Generation Z's musical creativity and innovation, using the theory of affordance as a theoretical foundation. The study employs a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on 219 respondents from West Papua and Papua provinces. The analysis results indicate that the intention to use AI (p = 0.000) and positive perceptions of AI in general (p = 0.000) have a significant influence on AI-based musical creativity, with moderate predictive power (R² = 0.461). This creativity was then found to encourage the use of AI in musical activities (p = 0.000) and the music creation process (p = 0.000), although both showed weak predictive power (R² = 0.292 and R² = 0.251). Conversely, awareness of AI (p = 0.509) and perceptions of AI in the context of music education (p = 0.135) did not significantly influence creativity. These findings suggest that positive intentions and perspectives toward AI are more decisive in driving creativity than awareness levels. Therefore, a contextual approach to digital music education that encourages active exploration is needed to optimize the potential of AI in enhancing creativity.